The financial requirements of achieving gender equality and woman's empowerment - Chandrika Bahadur; Diane Elson; Caren A. Grown; Jessie Handbury (Levy Economics Institute of Bard College, 2006)
Although the Millennium Development Goals (MDGs) have been ratified in global and national forums, they have not yet been incorporated into operational planning within governments or international organizations. The weak link between the policies and the investments needed for their implementation is one barrier to progress. An assessment of the resources required is a critical first step in formulating and implementing strategies to achieve the MDGs. This is especially true for policies to promote gender equality and empower women. Although enough is known about such policies to implement them successfully, the costs of such interventions are not systematically calculated and integrated into country-level budgeting processes. Using country-level data, the paper estimates the costs of interventions aimed at promoting gender equality and women's empowerment in Bangladesh, Cambodia, Ghana, Tanzania, and Uganda. It then uses these estimates to calculate the costs of such interventions in other low-income countries. Finally, the paper projects the financing gap for interventions that aim directly at achieving gender equality, first for the five countries, and subsequently for all low-income countries.
Keywords: F3; H5; J16; O2; 330; Millennium Development Goals; gender equality; cost estimates; financing gap; gender mainstreaming; public expenditure; macroeconomic policy; overseas development assistance